Do Morals Matter? Presidents and Foreign Policy from Franklin D. Roosevelt to Trump - Waqar, Azhar (Journal of Professional Research in Social Sciences, 2024)
Joseph Nye’s book, titled "Do Morals Matter? Presidents and Foreign Policy from FDR to Trump" explores the role of morality and ethical considerations in shaping international relations and decision-making processes, especially in by evaluating the intersection of ethics in the US foreign policy. Joseph Nye is a prominent figure in discipline of International Relations, known for co-founding the theory of neoliberalism, also as the proponent of the concept of soft power.